Analysis of difficulties of junior high school students in solving AKM numeration problems - Umam, Khoerul (SAINTIS Publishing, 2023)
Exploration of the difficulties faced by students in facing AKM exams is a challenge for teachers and practitioners of mathematics education. The main objective of this study is to map information about the difficulties students experience in carrying out AKM exams so that they can be used as evaluation material to prepare for better mathematics learning in the future. The selection of subjects was carried out randomly by considering good communication so that the data obtained could represent the population. Semi-structured interviews are used in collecting research data in order to create a more humane and conducive atmosphere. Data analysis used codes that had been reduced from the interview transcripts. The results of the research show that there are various challenges that need to get the attention of both teachers, students and parents of students. The loss of students' motivation in learning mathematics needs to get very serious attention for teachers and parents.